2017
DOI: 10.2337/dc17-0016
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding and Risk of Type 1 Diabetes in Two Large Scandinavian Birth Cohorts

Abstract: OBJECTIVEOur aim was to study the relation between the duration of full and any breastfeeding and risk of type 1 diabetes.RESEARCH DESIGN AND METHODSWe included two population-based cohorts of children followed from birth (1996–2009) to 2014 (Denmark) or 2015 (Norway). We analyzed data from a total of 155,392 children participating in the Norwegian Mother and Child Cohort Study (MoBa) and the Danish National Birth Cohort (DNBC). Parents reported infant dietary practices when their child was 6 and 18 months old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 30 publications
(45 reference statements)
4
61
1
3
Order By: Relevance
“…11,12 However, a recently published study involving children from the general population showed that no breastfeeding was related to an increased risk of diabetes compared with infants with history of any breastfeeding. 25 …”
Section: Discussionmentioning
confidence: 99%
“…11,12 However, a recently published study involving children from the general population showed that no breastfeeding was related to an increased risk of diabetes compared with infants with history of any breastfeeding. 25 …”
Section: Discussionmentioning
confidence: 99%
“…For the peanut studies, the LEAP study gave 6-g peanut protein per week, 30,31 whereas the EAT study used 4 g of peanut protein. 32 Timing of introduction of allergen solid(s)-the egg studies have all introduced this allergen at 4-6 months of age, [22][23][24][25][26] whilst the peanut study introduced the allergen from 4-11 months (mean 7.8 months). 27,28 In the EAT study, allergenic foods were introduced between 4 and 6 months except for cow's milk which was introduced from 3 months.…”
Section: Study Details Resultsmentioning
confidence: 99%
“…The role of breast milk in the aetiology and prevention of T1DM is controversial, with certain studies showing a protective effect and others reporting predisposing or no effects at all. [13][14][15] In 15 Many factors, particularly the experimental designs of these studies and variations in breastfeeding patterns in different countries, could be responsible for these inconsistent results. However, studies that report weak or negative effects usually monitor breastfeeding to an imprecise degree, without considering whether breastfeeding is exclusive or complementary.…”
Section: Association Of Bioactive Molecules With Breastfeedingmentioning
confidence: 99%